Implementation of Discovery Learning Model in Social Arithmetic Learning for Middle School Students - Saputri, Rama Nia; Susanta, Agus; Hanifah, Hanifah; Susanto, Edi (Jurnal Pendidikan MIPA, 2022)
This study aims to analyze the effect of the discovery learning model on student learning outcomes in social arithmetic material. This research is a quasi-experiment with a nonequivalent posttest-only control group design. The population of this study was seventh grade students of SMP Negeri 6 Bengkulu City. The sample was selected using the purposive sampling technique, namely class VIID as the experimental class with 20 students and class VIIC as the control class with as many as 23 people. Data was collected by using a social arithmetic material test. The data were analyzed descriptively and statistically by using an independent t-test. The results showed an effect of the discovery learning model on improving student learning outcomes in social arithmetic material. Statistically descriptive, the average student learning outcomes using the discovery learning model are higher than in conventional learning classes.Keywords: discovery learning, quasi experiment, learning outcomes.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1006-1016